Whole Exome Sequencing Identifies a Novel Pathogenic RET Variant in Hirschsprung Disease - Wu, Wei; Lu, Li; Xu, Weijue; Liu, Jiangbin; Sun, Jun; Zheng, Lulu; Sheng, Qingfeng; Lv, Zhibao (Frontiers in Genetics, 2019)
Hirschsprung disease is a birth defect characterized by complete absence of neuronal ganglion cells from a portion of the intestinal tract. To uncover genetic variants contributing to HSCR, we performed whole exome sequencing on seven members of an HSCR family. With the minor allele frequency (MAF) calculated by gnomAD, we finally filtered a total of 1,059 rare variants in this family (MAF < 0.1%). With the mode of inheritance and pathogenicity scores by bioinformatics tools, we identified an in-frameshift variant p.Phe147del in RET as the disease-causing variant. Further analysis revealed that the in-frameshift variant may function by disrupting the glycosylation of RET protein. To our knowledge, this is the first study to report the in-frameshift variant p.Phe147del in RET responsible for heritable HSCR.